(untitled) (Research, Society and Development, 2020)
Objective: to report the experience of two nursing students facing a case of schizophrenia in an elderly woman. Method: This is a descriptive, exploratory study of the type of experience report, which aims to observe and monitor a given situation and discuss it. The study was developed during the theoretical-practical discipline of mental health in the 2nd semester of 2018 of the nursing course in a residence located in the north of the city of Manaus, where home visits took place. Result: As future nurses, we understand how complex our role is in the face of this disease, but we also understand that these people need us, not only the patient but also his family. We need to be trained and sensitized with the history of these people. Conclusion: The competent bodies need to look at this cause. Investments in mental health have not met the demand. We need not only to treat the patient, but his family. The relatives of schizophrenic patients are tired, overwhelmed and often even become ill. And there are no effective public policies for these people. We cannot in any way throw all the weight on these families.